NIF (neurite-inducing factor): a novel peptide inducing neurite formation in PC12 cells - Wagner, JA (J Neurosci, 1986)
Neurite-inducing factor (NIF) is a novel protein that has been partially purified from mouse submaxillary glands. NIF induces neurite formation in PC12 pheochromocytoma cells, and the NIF-induced neurites are indistinguishable from NGF-induced neurites in both their morphology and the time course of their formation. Neurite-inducing activity can be recovered at a position corresponding to a molecular weight of 20,000 Da after fractionation of partially purified preparations via SDS-PAGE. Partially purified preparations of NIF are about half as potent as pure beta NGF, and since the neurite-inducing activity does not correspond to any of the major proteins in this fraction, specific activity of purified NIF will probably be significantly greater than the 60 ng/ml found for our partially purified material. NIF is distinct from beta NGF by four criteria: (1) antibodies to beta NGF can block the activity of beta NGF, but not the activity of NIF; (2) beta NGF can induce ornithine decarboxylase (ODC) in PC12 cells at concentrations significantly below those required to induce neurites, while NIF induces ODC only at concentrations greatly in excess of those required to induce neurite formation; (3) by the criterion of SDS-PAGE, there is insufficient beta NGF in our partially purified preparations of NIF to explain the biological activity of this fraction; and (4) the biological activity of NIF has a molecular weight (20,000 Da) that is distinct from beta NGF (13,000 Da). We conclude that NIF is probably a novel peptide that is very active in promoting morphological differentiation.(ABSTRACT TRUNCATED AT 250 WORDS)